La jalousie dans Les Diversitez de Jean-Pierre Camus - Pietrzak, Witold Konstanty (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Literary career of Jean-Pierre Camus started with his admiration for Montaigne’sEssais which became the pattern of his first work, Les Diversitez. The tome IX of this rich collectionof various forms concerns passions of the soul and scholars are unanimous in consideringit as the foundation of his religious teaching, both by word and by writing. Contrary to medicaland moral thought in force at the threshold of modernity, the bishop of Belley believespassions are neutral, neither good nor bad, and acquire their meaning by the use man makesof them. This is in particular the case of jealousy which the writer understands as an effect oflove. Yet in his treaty of passions the author describes on just several pages only the jealousyof God and for more details he refers the reader to two other places of Les Diversitez where, hesays, he has already raised the issue of this feeling. In fact, a chapter of the tome II and a letterof the tome VIII deal with the problem of human jealousy. This paper first shows different discursiveforms that Camus uses to analyze jealousy. Then it focuses on the author’s definition ofjealousy, ‘desire for exclusive possession of the loved object’, and on its effects – often tragical,always painful – in the daily life of spouses. Finally, it appears that the author’s taste for dichotomouspresentation of passions leads him to childish images of jealous God and implicitly toan inacceptable hypothesis of jealousy of the creature in front of a supposedly unfaithful God.